A systematic review of heat recovery from roads for mitigating urban heat island effects: current state and future directions - Ali, Moiz; Bicer, Yusuf; Al-Ansari, Tareq; Amhamed, Abdulkarem I. (Frontiers in Built Environment, 2023)
Heat recovery from roads is a promising technology to address the urban heat island effect. This review paper aims to provide a comprehensive analysis of the current state and future directions of heat recovery from roads to address the urban heat island effect while generating renewable energy. The study covers various aspects such as theoretical background, economic feasibility, environmental impact, and materials design techniques. A systematic search of relevant literature was conducted to analyze and synthesize different heat recovery systems' efficiency, performance, and potential. The paper also discusses the economic feasibility and environmental impact of these systems, including installation and maintenance costs, revenue generation, and local ecosystem impact. The review explores the role of different materials, such as PEX pipe, asphalt mix, and carbon nanotubes, in improving heat harvesting systems' efficiency. The paper concludes with a discussion of research gaps and future directions in the field of heat recovery from roads. This study provides a valuable resource for researchers, practitioners, and policymakers interested in sustainable and efficient energy system development.-Comprehensive analysis of the potential of heat recovery from roads to address urban heat island effect and generate renewable energy.-Coverage of various aspects, including theoretical background, economic feasibility, environmental impact, and materials design techniques.-Exploration of different materials, such as PEX pipe, asphalt mix, and carbon nanotubes, in improving heat harvesting systems' efficiency.-Discussion of research gaps and future directions in the field of heat recovery from roads.